MEMANEN PADI DI CUPAK KABUPATEN SOLOK DALAM KARYA SENI GRAFIS STENCYL PRINT - EGA PUTRA MELAYU, Yofita Sandra, S.Pd., M.PD., Drs. Abd. Hafiz, M.Pd (Serupa The Journal of Art Education, 2019)
The creation of this final work aims to visualize the situation of harvesting rice in Solok District Cup in a stencil print this work. displaying the traditional rice harvest atmosphere, which still survive. The method and process of work used in the creation of this printing making through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of the Concept, (5) Completion. The results of the visualization of West Sumatra children's games in this graphic work are 10 works with the title : (1) pai manongkang, (2) manyabik padi, (3) malambuik padi, (4) malambuik padi ka batu, (5) maangin,(6) manyukek,(7)mintak padi,(8)tukang angkek padi,(9) pancari jarami, (10)mangirai.Keywords: harvest rice. traditional, cupak, graphic arts.